Death and institutions : processes, places and the past - Woodthorpe, Kate; Frisby, Helen; Michael-Fox, Bethan (Bristol : Bristol University Press, 2025)
Institutions play a crucial role in shaping experiences of end-of-life care, dying, death, body disposal and bereavement. However, there has been little holistic or multidisciplinary research in this area, with studies typically focusing on individual settings such as hospitals and cemeteries, or being confined to specific disciplines. This interdisciplinary collection combines chapters on process, place and the past to examine the relationships both within and between institutions, institutionalization and death in international contexts. Of broad appeal to students and academics in areas including social policy, health sciences, sociology, psychology, anthropology, cultural studies, history and the wider humanities, this collection spans multiple disciplines to offer crucial insights into the end of life, body disposal, bereavement and mourning.
Front Matter -- Contents -- Series Editors' Preface -- List of Figures and Tables -- Notes on Contributors -- Acknowledgements -- Introduction -- Culture as an Institution: Assessing Quality of Death in China -- The Market for Human Body Parts: Institutions, Intermediaries and Regulation -- Secrecy, Judgement and Stigma: Assisted Dying in Aotearoa New Zealand -- Institutional Thoughtlessness: Prison as a Place for Dying -- Out of the Ashes in New York City: Body Storage Bottleneck in COVID-19's First Wave -- Governing the Dead's Territory -- 'The Bluecoat Boys to Walk and Sing an Anthem before the Corpse': The Children of Christ's Hospital in London Funerals of the 18th Century -- Inside-Out and Outside-In: Learned Institutions and Garden Cemeteries in 19th-Century Britain -- 'They Attached No Blame to the Staff in Charge': The Role of Dublin Workhouse Administration in Preventing and Contributing to Institutional Mortality, 1872-1913 -- Tenets and Tensions: A Critical Exploration of the Death Positive Movement -- Representations of Immortality and Institutions in 21st-Century Popular Culture -- 'I Was So Lost ... And Who Brought You Back? Me.': Deathstyle Gurus and the New Institutional Logics of Mourning on Instagram -- Afterword -- Index
Print version record.
JSTOR
Keywords: Death; Bereavement; Bereavement -- Psychological aspects; Death (Biology); Death -- History; Ethnology -- Death; Deuil; Deuil -- Aspect psychologique; Mort (Biologie); mourning; SOCIAL SCIENCE / Death & Dying